Pass-through, vertical contracts, and bargains - Germain Gaudin (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
This paper analyzes the determinants of pass-through that are specific to vertical relationships between wholesalers and retailers. Fluctuations in input costs (due to, e.g., exchange rate shocks) are transmitted first to the wholesale price, and then to the retail price. The type of vertical agreement firms contract upon as well as their relative bargaining power are identified as major determinants of pass-through rates. The relationship between passthrough rates at the wholesale and retail levels is also investigated. Finally, the result of Bresnahan and Reiss (1985) on markup ratio is extended to the case where firms bargain over the wholesale price.
Keywords: F31; L11; L81; 330; Pass-through; Exchange Rate; Vertical contracting; Bargaining